Visual Communication in Social Media: Generation Z’s Motivations and Social Impacts of Using Biaoqingbao on WeChat - Wu, Jiabao; SANTOS, Luis Miguel DOS; Kwee, Ching Ting Tany (Journal of Social Science and Humanities, 2025)
In the digital age, the widespread use of social media and instant messaging applications has prompted Generation Z to adopt increasingly diverse and visually oriented modes of communication. As a uniquely Chinese form of visual language, Biaoqingbao has not only transcended the limitations of textual expression on platforms like WeChat but also plays a central role in emotional expression, identity formation, and cultural affiliation. While previous studies have examined the cross-cultural use and linguistic functions of emojis, empirical research on the psychological motivations and usage patterns of Biaoqingbao among China’s Generation Z remains limited. This study employs Self-Determination Theory as a theoretical framework to investigate the practices of nine Chinese Gen Z users on WeChat, using (1) participant observation, (2) semi-structured interviews, and (3) focus group discussions. The findings reveal that Biaoqingbao serves not only as a tool for emotional expression but also as a strategy for fulfilling users’ psychological needs for autonomy, competence, and relatedness. Moreover, Biaoqingbao facilitates identity performance, social bonding, and subcultural affiliation, functioning as a key medium of symbolic interaction and cultural participation in the digital era. This study contributes to the theoretical understanding of visual communication and offers practical insights for platform designers, communication professionals, and social psychologists working with digitally native youth.